TBS-pyrrole as an “universal” reference to quantify artemisinin and structurally-diverse natural products in plants extracts by NMR - García-García, Ana L.; Hernández, Dácil; Santana-Mayor, Álvaro; Jiménez-Arias, David; Boto, Alicia (Frontiers in Plant Science, 2023)
The commercial production of artemisinin and other valuable bioactive natural products depends on their plant sources, which may provide variable amounts of the compound depending on plant variety, the period of the year, abiotic stress and other factors. Therefore, it requires a method for large-scale, low-cost natural product quantification. The standard HPLC and UHPLC methods are accurate but the analysis are costly and require different optimization for structurally-diverse products. An alternative method using NMR with TBS-pyrrole as a novel “universal” reference affords a simple, fast method to quantify many different products. The method is shown with antimalarial artemisinin, whose yield using conventional and novel extraction procedures was determined by standard UHPLC-MS procedures and by our NMR protocol, with similar quantification results. The novel reference compound does not interfere with artemisinin or extract signals, only needs a small amount of the extract, is accurate and operationally simple, and a large volume of samples can be processed in little time. Moreover, bioactive terpenes, steroids, alkaloids, aromatic compounds, and quinones, among others, were quantified in a model vegetal extract with this “universal” reference with excellent accuracy.